DEMOGRAPHIC SPASMS – A LIMIT OF SUSTAINABLE TERRITORIAL DEVELOPMENT. CASE STUDY: THE DISTRICT OF CICEU - Alexandra-Camelia POTRA (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
Demographic Spasms – A Limit of Sustainable Territorial Development. Case Study: The District (“Ținut”) of Ciceu. Human component is currently the most precious resource, the only one which can generate production and consumption, fact that makes it play an important part in the sustainable development of the territorial unit it occupies. However, we know that most of the changes take place at the level of this component, of action and interaction, usually materialized in malfunctions, in demographic spasms constraining the support and deign of a certain trend of development. Starting from this assumption, in this study, we analyzed the demographic spasms manifested in the District of Ciceu, a rural micro-region located in the central part of the North-West Development Region, where the decline of the population, especially the young one, as a result, distinctly or cumulated, of several mechanisms, has increased the imbalances between the age groups, leading to an increase of the economic dependency ratio and the age dependency ratio, a situation that raises serious questions as it appears that the population is below the limit required to support the sustainable development of this unit.